The 2016 Mw 7.1 Kumamoto Earthquake A Photographic Atlas of Coseismic Surface Ruptures Related to the Aso Volcano, Japan - Lin, Aiming (Springer Singapore, 2018)
This book shows the deformation characteristics of coseismic surface ruptures produced by the 2016 Kumamoto earthquake and the relationship between the Aso volcano and active faults. In particular, the rupturing mechanisms and processes involved in the seismogenic faults related to the crustal structure under the Aso volcano caldera are covered. The book is intended to help bridge the gaps between seismology, seismic disaster prevention, volcanology, seismotectonics, and geology and to encourage further studies of earthquake mechanisms and seismic faulting processes.